Audiometry-Confirmed Sudden Sensorineural Hearing Loss Incidence among COVID-19 Patients and BNT162b2 Vaccine Recipients. Issue 2 (21st February 2023) - Cohen Michael, Ori; Tamir, Sharon Ovnat; O'Rourke, Norm; Marom, Tal
Abstract : Objective: To compare sudden sensorineural hearing loss (SSNHL) incidence rates over the coronavirus disease 2019 (COVID-19) outbreak and the COVID-19 vaccination campaign periods to pre-COVID-19 periods. Study Design: Retrospective cohort. Setting: Secondary hospital. Patients: Patients >12 years with auditory-confirmed SSNHL were enrolled. COVID-19 status and BNT162 inoculation records ≤28 days before SSNHL diagnosis were retrieved. Patients were categorized according to their date of presentation over four equal periods: 1) July 2018–April 2019 (first prepandemic period), 2) May 2019–February 2020 (second prepandemic period), 3) March 2020–December 2020 (COVID-19 outbreak), and 4) January 2021–October 2021 (BNT162b2 vaccinations campaign). Interventions: Pre- and post-COVID-19 emergence; BNT162b2 vaccine. Main Outcome Measures: Incidence rate ratios (IRRs) were calculated to compare SSNHL cases during the COVID-19 and vaccination periods with pre-COVID-19 periods. Results: Of the 100 patients with SSNHL over the four periods, 1 had COVID-19 and 8 were vaccinated. The annual SSNHL incidence was 12.87, 12.28, 13.45, and 19.89 per 100, 000 over periods 1 to 4, respectively. SSNHL incidence over the third period was not significantly different than the first/second periods (IRR = 1.045, 95% confidence interval [CI] = 0.629–1.85, ρ = 0.788, and IRR = 1.095, 95% CI = 0.651–1.936, ρ = 0.683, respectively), whereas SSNHL incidence rate over the fourth period was higher (IRR = 1.545, 95% CI = 0.967–2.607, ρ = 0.068, and IRR = 1.619, 95% CI = 1–2.73, ρ = 0.05, respectively). SSNHL incidence in vaccine recipients was lower than prepandemic unvaccinated patients (IRR = 0.584, 95% CI =0.464–1.67, ρ = 0.984, and IRR = 0.612, 95% CI =0.48–1.744, ρ = 0.92, respectively). Conclusion: There were fewer SSNHL cases during the first COVID-19 months. Although the SSNHL rate over the COVID-19 vaccination campaign increased, it was not higher for patients who received the BNT162b2 vaccine.